NNESTs v.s. NESTs: Why Domestic English Teachers Should Not Worry about Their Foreign Counterparts - Amalia, Syahara Dina (Sebelas Maret University, 2016)
Not few renowned English courses have hired foreign English teachers to gain more learners, so do formal schools or universities. Some of the teachers are hired professionally, and some are volunteers as a part of an agreement between the institution and a non-profit organization to teach in developing countries. The presence of foreign English teachers or commonly known as NESTs (Native English-Speaking Teachers) in many Indonesian educational institutions is inevitable. Yet, so many pros and cons have shadowed their existence in ELT classes. Some people problematize their being overpaid and other question their educational background or teaching experience despite their being native. This phenomenon has created a gap between NESTs and their domestic counterparts. What are they supposed to think? Should domestic English teachers or known as NNESTs (Non-Native English-Speaking Teachers) be worried about this phenomenon? This paper tries to evaluate this phenomenon from several different points of view, especially with regards to the current status of English as a global language.